2003
DOI: 10.1097/01.ju.0000076001.21606.53
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ascorbic Acid Consumption On Urinary Stone Risk Factors

Abstract: Ingestion of 2 gm AA daily results in no change in urinary pH but a moderate though statistically significant increase in urinary oxalate in NS (20%) and SF (33%). Stone formers respond no differently to AA than normal subjects. We recommend limiting AA use to less than 2 gm daily in CaOx stone formers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(96 citation statements)
references
References 20 publications
4
83
0
5
Order By: Relevance
“…Another metabolic trial demonstrated that 1000 mg of supplemental vitamin C consumed twice daily increased urinary oxalate excretion by 20 to 33%. 23 To our knowledge, only two previous studies that used direct analytical techniques to measure food oxalate attempted to quantify the oxalate content of the typical Western diet. One study consisted of five healthy individuals (mean age 29 yr), and the mean oxalate intake, as measured by a 3-d dietary record, was 152 mg/d.…”
Section: Discussionmentioning
confidence: 99%
“…Another metabolic trial demonstrated that 1000 mg of supplemental vitamin C consumed twice daily increased urinary oxalate excretion by 20 to 33%. 23 To our knowledge, only two previous studies that used direct analytical techniques to measure food oxalate attempted to quantify the oxalate content of the typical Western diet. One study consisted of five healthy individuals (mean age 29 yr), and the mean oxalate intake, as measured by a 3-d dietary record, was 152 mg/d.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44] Patients and physicians have expected to overcome chronic disease such as cardiovascular disease or cancer by consumption of vitamin C, based on its antioxidant activities. 45 Previous studies were not able to show any benefit regarding the consumption of vitamin C and cancer prevention, urinary stone production 47 and reduction of common cold incidence. [48][49][50] Lee et al assessed the association between intake of vitamin C and mortality from cardiovascular disease in 1923 diabetic postmenopausal women.…”
Section: Vitamin Cmentioning
confidence: 99%
“…The results of many feeding studies may have limited applicability to free-living populations. For example, although 1000 mg of supplemental vitamin C consumed twice daily increases urinary oxalate excretion by 22% (11), the effect of lower, more commonly consumed doses of vitamin C on urinary oxalate excretion is uncertain. Previous population-based studies have been relatively small and provide conflicting results about the associations between vitamin C intake, body size, and urinary oxalate (12,13).…”
mentioning
confidence: 99%